Management of Oral Health During Pregnancy - Narottam Praharaj1 , Debasruti Naik2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Good oral health is an important aspect towards overall health for all the women throughout their lifespan.For every expecting women and also women those who are of reproductive age, for them health status oftheir oral cavity is very much an important module of the general health. During pregnancy there is a rapidphysiologic change that leads to occurrence of remarkable strain on a woman’s body together with the oralcavity. Both intended for mother and children, maintaining and achieving good oral health is very important.There are evidences that poor wellbeing of the mother such as dental decay, periodontal diseases previousto and during pregnancy have been linked to poor birth for example preterm birth and low birth weight.Oral health is a significant part of overall health. During pregnancy, an expectant women goes through lotof hormonal changes and these hormones sometimes increase the risk of gingival diseases that will hamperthe health of any would me mother and might increase the menace of premature delivery or low birth weightinfant. It is very much necessary that oral health care need should be recognized for every pregnant womenand it is also the sole responsibility of every pregnant women that they should feel responsible care of theiroral health as an important aspect of their pregnancy course. This review article highlights the importance ofhealth of oral cavity for all expectant pregnant women.